My carrel, my second home: Inclusion and the sense of belonging among visually impaired students in an academic library - Bayat Bodaghi, Nahid; A.N., Zainab; Bayat Bodaghi, Nahid; Zainab, A.N. (Malaysian Journal of Library and Information Science, 2017)
Bayat Bodaghi, N., & Zainab, A. N. (2013). My Carrel, My Second Home: Inclusion and the Sense of Belonging Among Visually Impaired Students in an Academic Library. Malaysian Journal of Library & Information Science, Vol.18, no. 1: 39-54. This paper explores visually impaired persons’ (VIPs) sense of belonging in a university library context. It focuses on their perceptions of and experiences with study carrels located in the university library. Data were collected during interviews and focus group discussions. Participants consisted of five female and thirteen male students between the ages of 20 and 37 years. Participants considered their carrels as second homes where they felt safe, comfortable, and accepted. The carrels gave them a sense of belonging. The carrels also served as social places where the VIPs could interact with peers, volunteer readers, and other sighted students. The VIPs viewed their carrels as quiet havens where they could study and learn. They felt they belonged to the library community and were proud to be accepted as students at the university. The findings may increase library managements’ awareness of the need to include these types of spaces in future design.